ANALISIS RESPONS BUTIR PADA TES BAKAT SKOLASTIK - Setiawati, Farida Agus; Izzaty, Rita Eka; Hidayat, Veny (Faculty of Psychology, Diponegoro University, 2018)
This study aims to analyze the characteristics of the Scholastic Aptitude Test (SAT), consisting of both verbal and numerical subtests. We used a descriptive quantitative approach by describing the characteristics of SAT based on the degree of item difficulty, item discrimination index, pseudoguessing index, test information function and standard error measurement. The data are responses of the SAT instrument, collected from 1,047 subjects in Yogyakarta using the documentation technique. Data were then analyzed by Item Response Theory (IRT) approach with the help of the BILOG program on all logistic parameter models, preceded by identifying item suitability with the model. Analysis concludes that: verbal subtest tends to compliment the 2-PL and 3-PL model, meanwhile, numerical subtest only fit the 2-PL model. Majority items of SAT have a good characteristic on index of item difficulty, item discrimination, and pseudoguessing, and based of test information function, SAT is accurate to be used in the 1-PL, 2-PL, and 3-PL IRT models for all level of ability.